Using Wayground as a Cognitivist Learning Medium to Teach Nahwu: A Descriptive Study on the Implementation of Pedagogy and Students’ Perception - Abdul Muid; Uril Bahruddin; Isnainiyah Isnainiyah; Miftahus Sa'diyah; Budi Santoso; Ahmad Fikri (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2026)
Background: Nahwu learning often faces challenges due to students’ low motivation and difficulties in understanding abstract grammatical concepts. These challenges are frequently intensified by traditional teaching approaches that lack interactivity and provide limited opportunities for active practice with grammatical rules. Research Objectives: This study aims to describe the implementation of Wayground in nahwu learning based on cognitivist theory and to examine students’ attitudes toward its use. Methodology: This study employed a qualitative approach supplemented by quantitative descriptive data on student perceptions. Conducted at Madrasah Aliyah Darul Qiyam Kerinci, it involved 40 twelfth-grade students selected through total sampling. Data were collected through observation, documentation, and a four-point Likert-scale questionnaire, and analyzed descriptively and thematically using frequencies, percentages, means, and standard deviations. Results: The implementation of Wayground-based nahwu learning consisted of five stages: (1) preparation of materials and quizzes, (2) activation of prior knowledge, (3) guided use of Wayground, (4) interactive quizzes, and (5) feedback through discussion. These stages reflected cognitivist principles, including schema activation, information processing, repetition, reinforcement, and immediate feedback. Students responded positively, reporting that Wayground helped them understand nahwu concepts, organize grammatical information, connect new knowledge with prior knowledge, and increase motivation and confidence. Unique Contribution: This study contributes to technology-supported nahwu learning by demonstrating the pedagogical integration of Wayground with cognitivist theory and offering a theoretically grounded instructional approach that does not claim causal effectiveness. Conclusion: Wayground can function as a useful supplementary tool for cognition-based Nahwu learning when supported by structured instructional stages, carefully designed questions, teacher facilitation, and follow-up discussions. However, positive student perceptions should not be interpreted as direct evidence of improved learning outcomes. Recommendations: Future research should involve larger samples, different nahwu topics, and more rigorous designs, such as pretest/posttest or comparative studies, to more directly assess its impact on students’ achievement and cognitive development.